AKUNTABILITAS DANA DESA (Studi Fenomenologi Dana Desa di Desa Salam, Kecamatan Grabag, Kabupaten Magelang, Jawa Tengah) - Vina Fauziah; Warsito Kawedar (Diponegoro Journal of Accounting, 2020)
This study aims to assess the accountability in the management of the Village Fund in Salam Village Grabag Sub-district Magelang Regency, Central Java. Accountability was choosen as the main topic of the research because accountability is a form of government responsibility for the program of activities that implemented. The research method that used in this study is a descriptive qualitative research method with a phenomenological approach. Data collection techniques are carried out through in-depth interviews and direct observation in the field and gathering supporting evidence. The interwiews conducted were semi-structured interviews with some village officials as a managers of the Village Fund and some community representative institutions from all hamlets in Salam village, Grabag sub-district, Magelang regency, Cebtral Java. The total informants in this study were 9 people. The type of the data used in this research are primary data that obtained through in-depth interviews with informants, and secondary data in the form of documents and photographs that obtained during direct observation. The result showed that the management of the Village Fund conducted by the Salam village government was accountable in accordance with the Minister of Home Affairs Regulation Number 113 of 2014 concerning village financial management, both from the planning stage to its reporting. Salam Village government is also a government with good governance in terms of Village Fund management.